Relational Justice in Islamic Inheritance Law: Reinterpreting Gender Equality Through the Thought of Husein Muhammad and Faqihuddin Abdul Kodir - Moch. Aufal Hadliq Khaiyyul Millati Waddin; Sri Lumatus Sa’adah; Pujiono; Imam Bonjol Jauhari (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Purpose – This study examines the concept of relational justice in Islamic inheritance law in response to the growing tension between classical legal doctrines and contemporary transformations in gender roles within Muslim societies. While existing studies have explored gender justice, maqāṣid al-sharī‘ah, and mubādalah approaches, an integrated theoretical framework for reinterpreting inheritance distribution remains underdeveloped. This research aims to formulate relational justice as a conceptual framework that bridges classical Islamic legal principles and contemporary socio-economic realities. Method – This study employs a qualitative normative–conceptual approach grounded in maqāṣid al-sharī‘ah and legal hermeneutics. Primary sources include Qur’ānic verses on inheritance (Q.S. al-Nisā’: 7, 11, 12, and 176), relevant ḥadīth, and provisions of the Kompilasi Hukum Islam (KHI), supported by both classical and contemporary scholarship. Data were analyzed using thematic analysis, legal hermeneutics, and maqāṣid-based reasoning. Findings – The findings reveal that classical distributive paradigms—particularly the 2:1 inheritance ratio—are historically grounded in gendered economic responsibilities that have shifted in contemporary contexts. Relational justice offers a context-sensitive framework by emphasizing social relations, reciprocal responsibilities, and actual economic contributions within the family. This framework enables reinterpretation while remaining aligned with the ethical objectives of Islamic law. Research Implications – This study is limited to normative and conceptual analysis and does not include empirical investigation. Future research is needed to examine the application of relational justice in judicial practices and within Muslim societies. Originality/Value – This study contributes by proposing relational justice as a distinct theoretical framework that integrates maqāṣid al-sharī‘ah, emancipatory fiqh, and qirā’ah mubādalah into a coherent analytical model, offering a more contextual approach to Islamic inheritance law.